Daya Saing Industri Furnitur Indonesia dalam Perdagangan Global: Studi Komparasi dengan Vietnam - Muhammad Haidar Daulay; Emma Soraya; Ahmad Maryudi (Jurnal Ilmu Kehutanan, 2022)
Furniture products with significant added value are strategic commodities for the Indonesian economy. Therefore, this research aimed to determine the competitiveness of the Indonesian furniture industry in terms of marketing by making a comparison with Vietnam due to being one of Indonesia's main competitors in the furniture trade for decades. This research employed a literature study to collect data and an integrated comparative analysis using the 5P mixed market framework of position, product, place, promotion, and price. The results showed that both countries had similar market segments with sensitivity to illegal timber, for example, the US and EU. Vietnam was exceptional in offering lower prices since the Vietnamese furniture industry gained substantial support from the availability of abundant cheap labor and investment. Meanwhile, Indonesia was eminent in supplying raw materials from production forests, and its furniture industry had reached an augmented products level greater than Vietnam. Both countries have easy access to global shipping. Concerning promotion, Indonesia ought to emulate Vietnam by facilitating the furniture industry to participate in international exhibition activities to expand the furniture market network.